IMPLEMENTATION OF THE EPHORUS ELECTION OF CHRISTIAN BATAK PROTESTAN (HKBP) 2016 - Daniel Partahi Oloan Panggabean; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2018)
This study aims to determine the Electoral System used in the Ephorus HKBP election, the stages used in the selection of Ephorus through 5 (five) key stages of the Election and the Election Organizing Model used in the 2016 HKBP Ephorus Election.This type of research is a type of case study research through a qualitative approach. Source of data used in the form of primary data derived from the results of indepth interviews with informants and secondary data in the form of archives and documentation.This study found the Electoral System used in the Ephorus Selection was the Two Round System (TRS) Election System with Vote Counting with the Kuesquisent system namely the number of voters divided by the number of candidates. Unlike the Praeses Election that uses the Block Vote System (BV), the vote counting is done through ranking instead of candidates who achieve absolute/ majority votes as much as 50%+1. Then in 5 (five) key Elections, namely the List of Voters, candidates, campaings, Voting and Vote Counting and Determination of Elections results. And the Electoral implementation Model used is an independent Organizing Model but does not have a Body to regulate the policy and implementation of the Election but only done by the Synod Godang HKBP Committee.The results of this study recommend that the election of Ephorus be maintained between the mixing of Protestant Christianity and the Toba Batak Tribe and produce an Election System that has never been studied before.Keywords : Election, Ephorus Election, HKBP